Gender representation and related effects in planning for rural development - Kim Pollermann; Lynn-Livia Fynn (ZBW - Leibniz Information Centre for Economics, 2022)
In rural development, the issue of female representation has become part of the agenda in Germany. To examine the topic of gender representation and the results arising from different programming strategies/approaches, we analyse empirical data from the evaluation of LEADER which forms part of Rural Development Programmes in the EU. LEADER is a place-based and participatory approach which involves a Local Action Group (LAG) composed of stakeholders from local government, civil society and economy steering the implementation of its local development strategy. To examine gender aspects within LEADER, we utilise results from the 2014-2020 funding period, especially structural data of 115 LAGs in four federal states in Germany. Main material was collected by means of three surveys, using written questionnaires (LAG member survey, LAG management survey, survey of beneficiaries). Regarding results, we looked at the share of females in the decision-making bodies of LAGs. The results for different federal states range from 26 % to 42 %. Thereby, there is a (slight) increase in the share of females is observed in all four federal states in comparison with previous funding periods. The highest share of 40 % can easily be explained : it was the only federal state with a fixed quota (one third of board members had to be females). The other three federal states also address the topic but only make soft regulations like "there should be a balanced gender representation" - which leads to mixed results in the composition of board members. However, it is also observed that the federal state with the weakest requirements has the lowest female representation. We further examine the consequences of gender representation for decision-making within the LAGs, whereby a gender gap in social preferences and priorities is confirmed.
Conference: Regions in Recovery Second Edition 2022: Re-imagining Regions, 21 March 2022, Regional Studies Association, Online
Keywords: R58; 330; LEADER; rural development; gender